Misfitting Mothers: feminism, disability and motherhood - Robertson, Rachel (Hecate Press, 2015)
The claim that, "feminist scholarship and disability studies scholarship are natural partners" (Piepmeier, Cantrell and Maggio, np), is an increasingly common one. Over the last decade, a number of scholars (Garland-Thomson; Kafer; Lloyd; Wendell) have called for feminist thought to integrate the insights of critical disability studies and for disability studies to gain from taking a feminist approach. My interest is in how a feminist approach to motherhood can gain from disability studies. In this article, I use one particular feminist disability concept-the concept of "misfit" as elaborated by Rosemarie Garland- Thomson ("Misfits")-to demonstrate how disability theory might illuminate certain experiences of mothering.